REGARDING REWARDS AND PENALTY PRACTICES IN THE CLASS MANAGEMENT PROCESS TEACHER OPINIONS - PARİN , Mehmet (SSD Journal, 2024)
In this study, it was aimed to determine the situations of teachers applying reward and punishment in the classroom management process. The study group of this research, which is a qualitative study, consists of 23 teachers from different branches working in secondary education institutions within the body of Antalya Kepez District National Education Directorate. The participants of the research were formed by the maximum diversity method. The data of the research were collected through a semi-structured interview form, which is a qualitative data collection tool. In the semistructured interview form, which was created by taking expert opinion, the teachers were asked "What are the main undisciplined behaviors of the students in classroom management?", "How and in what way do reward and punishment practices take place in the classroom management process?" have an effect on their behavior?'', ''Which rewards and punishments do you use most in order to regulate the behavior of students in the classroom?'' and ''What alternative practices can be used instead of rewards and punishments in classroom management?'' were asked. Interviews with the participants were recorded on a voice recorder. The data obtained from the interview were analyzed with qualitative data analysis methods and the interview data were defined and interpreted. In the findings obtained as a result of the research, the main undisciplined behaviors of the students are titled as the student's not knowing how to behave in the classroom, being indifferent to the school and lessons, and disrespectful towards his teachers and friends. In the second sub-problem, the most used reward application by the teachers is rewarding with a grade when the student shows positive behavior. Punishment was observed to be in the form of verbal warning when the student exhibits undesirable behavior. In the third sub-problem, the teachers stated that the reward had an effect on the behavior and the punishment had little or no effect on the behavior. In the fourth sub-problem, it was seen that teachers mostly used grades and psychological rewards as rewards, and psychological punishment the most as punishment. In the last sub-problem, it was observed that teachers did not have enough or no knowledge about alternative practices instead of rewards and punishments in classroom management. Teachers should be informed about the measured use of reward and punishment, which is a behavior control mechanism, in the classroom management process, and the possible negativities that may arise as a result of the use of reward and punishment. In classroom management, teachers should undergo in-service training on which alternative practices can be applied instead of rewards and punishments.Finally, for an effective classroom management, it is necessary to enrich the classrooms with materials and improve their physical conditions in order to teach the lesson with student-centered, activity-based methods and techniques.